2021
DOI: 10.1088/1742-6596/1719/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

Sound absorption properties of rigid polyurethane foam composites with rubber-wood sawdust as a natural filler

Abstract: Rigid closed-cell polyurethane (PU) foam is well-known for its ability to withstand external force. On the other hand, due to the closed-cell nature, its ability to absorb sound is doubtful since hollowed materials are supposed be better in sound absorption. However, the composites fabrication with non-reactive fillers was thought to improve sound absorption ability since it might prohibit the formation of closed cell in the process. In this research, rigid polyurethane foam was prepared from polyether polyol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Generally, mycelium composites are good thermal, and acoustic insulators: their thermal conductivity ranges from 0.04 to 0.18 Wm −1 K −1[ 1 ] and they can absorb up to 75% sound at frequencies below 1.5 kHz [ 41 ] with a typical Noise‐Reduction‐Coefficient (NRC) of 0.4–0.53. [ 42 ] In comparison, commercial acoustic foams like HDPU can absorb up to 90% sound within the same frequency range, [ 43 ] and have a NRC of ≈0.644. [ 41 ] The thermal stability and fire‐retardant properties of mycelium composites are quite poor, like other bio‐based materials.…”
Section: Mycelium Composites: An Overviewmentioning
confidence: 99%
“…Generally, mycelium composites are good thermal, and acoustic insulators: their thermal conductivity ranges from 0.04 to 0.18 Wm −1 K −1[ 1 ] and they can absorb up to 75% sound at frequencies below 1.5 kHz [ 41 ] with a typical Noise‐Reduction‐Coefficient (NRC) of 0.4–0.53. [ 42 ] In comparison, commercial acoustic foams like HDPU can absorb up to 90% sound within the same frequency range, [ 43 ] and have a NRC of ≈0.644. [ 41 ] The thermal stability and fire‐retardant properties of mycelium composites are quite poor, like other bio‐based materials.…”
Section: Mycelium Composites: An Overviewmentioning
confidence: 99%
“…Sound absorption is a physical phenomenon where sound wave energy is attenuated inside a material resulting in the reduction of wave energy. Chanlert et al, [6] defined that sound absorption as a part of a soundwave hitting a surface that does not reflect. There are many ways to attenuate sound waves such as increasing air resistance or even using destructive superposition between the incident waves and reflected waves.…”
Section: Introductionmentioning
confidence: 99%
“…The term 'acoustic material' is commonly used and applied for material showing high levels of sound absorption. To make an acceptable sound absorbing material, several factors affecting the sound absorption property of acoustic material should be concerned such as porosity, hardness, elasticity, or even surface morphology [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of natural fillers also plays an important role in this field due to their positive influence on several properties of RPUFs. In this sense, forest and agricultural residues stand out due to their high availability, low price, and high renewability [7], as well as good thermal [8] and acoustic [9] insulating properties. Furthermore, free hydroxyl groups (-OH) on the surface of these lignocellulosic matrixes give a high host chemical compatibility with RPUFs, since they are prone for binding to isocyanate groups (-NCO) from the polymer matrix [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most studied bio-based residues, wood flour is one of the most widely used fillers as reinforcement for polymer composites. For instance, Chanlert and Ruamcharoen [9] achieved improved sound absorption properties in RPUFs using a rubber wood-based sawdust as a filler. In a more recent study, De Luca Bossa and co-workers [7] reported increases in thermal stability and some mechanical properties, which were attributed to the incorporation of vegetable fillers, namely powdered cellulose and walnut shells.…”
Section: Introductionmentioning
confidence: 99%